On Numerical Methods for Solving Iterative Ordinary Differential Equations - Podisuk, Maitree; Suchatvejpoom, Suntorn; Chaisanit, Pornchai (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
In this paper, four numerical methods for solving iterative ordinary differential equations are introduced and used them to solve four examples. The results from each method are compared. Keywords: - E-mail: cast@kmitl.ac.th